The Role Of Quantum Electronics In Alternative Energy - Dilafruz Ahmadovna Mukhammadova (The American Journal of Applied Sciences, 2021)
The article deals with Quantum electronics, as a field of physics that studies methods of amplification and generation of electromagnetic radiation based on the phenomenon of stimulated radiation in nonequilibrium quantum systems, as well as the properties of amplifiers and generators obtained in this way and their application, a description of the structure of the most important lasers is given, physical foundations of quantum electronics, which are reduced primarily to the application of Einstein's theory of radiation to thermodynamically nonequilibrium systems with discrete energy levels. The article is intended for undergraduates of the Department of Physics, Radio Engineering, who have interests in the field of research and applications of laser radiation, and is aimed at giving them the minimum necessary for that initial information on quantum electronics.